Control Potential of Brassicaceae Cover Crops as Green Manure and their Host Status for Meloidogyne javanica and Criconemoides xenoplax - Kruger, D.H.M.; Fourie, J.C.; Malan, A.P. (South African Journal of Enology and Viticulture, 2016)
Laboratory bioassays were undertaken to determine the potential of Avena sativa cv. Pallinup (Pallinup oats), Sinapis alba cv. Braco (white mustard), Brassica napus cv. AV Jade (canola), Brassica juncea cv. Caliente 199 (Caliente) and Eruca sativa cv. Nemat (Nemat) to suppress Meloidogyne javanica (root-knot nematode) and Criconemoides xenoplax (ring nematode) when applied as green manure. The host status of the crops also was determined during glasshouse trials. Plant material of the different cover crops was macerated and mixed with nematode-inoculated soil. After a period of 14 and 28 days respectively, susceptible tomato plants were planted in the soil, where they were left to grow in a glasshouse, prior to the performance of a root gall index. The same procedure was followed for C. xenoplax, except that, in this case, the nematodes were extracted from the soil after 14 and 28 days to determine the impact of the plant biomass on nematode numbers. To determine the host status of the cover crops concerned, potted plants were inoculated with the two nematode species. Results from the bioassays showed significant suppression of M. javanica by white mustard, Caliente 199 and Nemat. However, no significant differences were found in the C. xenoplax bioassays. In the M. javanica glasshouse host trials, Nemat was classified as a poor host. In the C. xenoplax host trials, canola was found to have a suppressing effect on C. xenoplax. The results are the first to show the effect of biofumigation on C. xenoplax nematode.